The de Bunsen Committee and a revision of the ‘conspiracy’ of Sykes–Picot - Johnson, R (Taylor and Francis, 2018)
On a flight to Philadelphia, an ageing American of Palestinian origin insisted on a conversation. He regaled his neighbouring passenger with his reasons for supporting Donald Trump in his presidential campaign, citing his reason as the surprising claim that Trump would overturn Jewish interests prevailing in the capital. The gentleman then went on to extol the virtues of strong leadership, comparing Trump to the Egyptian nationalist leader, Gamal Abdel Nasser, but, after an hour of hagiography, he condemned only one thing: Nasser’s apparent unwillingness to tear up the Sykes–Picot Agreement. Interrogated further, he claimed this instrument of humiliation proved that the West had set out to subordinate the Arabs and set them against each other. But he admitted he knew very little of the details, except that, the ‘facts are widely known’. He seemed genuinely disappointed that Nasser had not ‘gone further’ and ‘united all Arabs’ and overturned Sykes–Picot.1 Such views are not uncommon across the Middle East.